Information and Communication Technology (ICT) and Banking Industry - Alawode, Ademola John; Kaka, Emmanuel Uche (Mediterranean Journal of Social Sciences, 2011)
Information and Communication Technology, the language of the new age and its grammar which is Science hasbecome an indispensable and veritable tool for enhancing effectiveness and efficiency in all other aspects of life. Bankingindustry has learnt the grammar and understands the language of the new age and tremendously transforms the Industry fromwhat it used to be to the economic mover of the whole wide world, through the magic hands of Computer Science innovations.The adoption of ICT in banks has improved customer services, facilitated accurate records, provides for Home and OfficeBanking services, ensures convenient business hour, prompt and fair attention, and enhances faster services. The adoption ofICT improves the banks’ image and leads to a wider, faster and more efficient market. It has also made work easier and moreinteresting, improves the competitive edge of banks, improves relationship with customers and assists in solving basicoperational and planning problems. This paper work analyses the impacts made by the Information and CommunicationTechnology in the Banking Industry, and some of the unexploited areas of the Information and Communication Technology in theindustry.